2020
DOI: 10.3390/en13184967
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Silica, Activated Carbon, and Alumina Supports on NiMo Catalysts for Residue Upgrading

Abstract: The effect of different supports such as silica (SBA-15), activated carbon (AC), and mesoporous alumina (Al2O3) on catalytic activities of hydrotreating nickel molybdenum (NiMo) catalysts was demonstrated for upgrading vacuum residue. Nitrogen adsorption-desorption analysis showed that SBA-15 and the AC-supported NiMo catalyst possessed a very high surface area compared to the alumina-supported catalyst. However, NiMo/Al2O3 catalyst possesses a higher pore diameter and pore volume with an appropriate surface a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 41 publications
(67 reference statements)
0
15
0
Order By: Relevance
“…This possibly resulted from the effect of catalyst acidity and the reaction condition (high temperature and H 2 pressure). Kohli et al 60 reported that the alumina support could promote the cracking of residue and VGO during the hydrotreating of the vacuum residue. However, no difference in product distribution obtained from the system using NiMo/γ‐Al 2 O 3 catalyst or NiW/γ‐Al 2 O 3 catalyst was observed, although the acidity of both catalysts was different.…”
Section: Resultsmentioning
confidence: 99%
“…This possibly resulted from the effect of catalyst acidity and the reaction condition (high temperature and H 2 pressure). Kohli et al 60 reported that the alumina support could promote the cracking of residue and VGO during the hydrotreating of the vacuum residue. However, no difference in product distribution obtained from the system using NiMo/γ‐Al 2 O 3 catalyst or NiW/γ‐Al 2 O 3 catalyst was observed, although the acidity of both catalysts was different.…”
Section: Resultsmentioning
confidence: 99%
“…These peaks can be attributed to MoO 2 or MoO 3 phases. 19 Overall, FeMocit-AC2 and FeMo-cit-TAC2 products show broad peaks with lower intensity indicating that their particle sizes are relatively small and there is substantial dispersion of active metal particles in the structure. When the metal particles spread more evenly, it is expected that agglomeration of the particles reduces leading to smaller particle sizes.…”
Section: Catalyst Characterizations 331 Xrd Analysismentioning
confidence: 98%
“…For instance, Kohli et al have studied the effects of various types of supports such as alumina, activated carbon, and silica on the performance of Ni–Mo catalysts for residue upgrading. Having found that the alumina support results in higher sulfur removal yield, they determined that the size and volume of the pores are directly related to the performance of the catalyst . In another work, the performance of the same catalyst for removing thiophene was studied by trying various types of support materials .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations